The Art and Science of Microelectronic Circuit Design - Belous, Anatoly; Saladukha, Vitali; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book guides readers through the entire complex of interrelated theoretical and practical aspects of the end-to-end design and organization of production of silicon submicron integrated circuits. The discussion includes the theoretical foundations of the operation of field-effect- and bipolar transistors, the methods and peculiarities of the structural and schematic design, basic circuit-design and system-design engineering solutions for bipolar, CMOS, BiCMOS and TTL integrated circuits, standard design libraries, and typical design flows. Provides a detailed description of the physical mechanisms and processes taking place inside the basic elements of design libraries; Shows how to control processes based on CMOS and bipolar technologies, that obtain the necessary values of operational speed, power consumption, electrical and dynamic parameters, and noise immunity of a specific integrated circuit; Introduces a new logic design algorithm for CMOS integrated circuits with extremely low power consumption.
1. Standard characteristics of digital microcircuits -- 2. Schematic solutions of digital cmos microcircuits -- 3. Schematic technical solutions of the bipolar integrated circuits -- 4. Circuit engineering of bicmos ic -- 5. Structure and specific features of design libraries for submicron microcircuits -- 6. Digital ic design flow -- 7. Fundamentals of cmos microcircuits logic design with reduced power consumption -- 8. Fundamentals of building a quality management system for manufacturing submicron integrated circuits based on test structures.
Keywords: Electronic circuits; Telecommunication; Electronics; Electronic Circuits and Systems; Microwaves, RF Engineering and Optical Communications; Electronics and Microelectronics, Instrumentation; Integrated circuits -- Design